Moth catcher - Cleeves, Ann (London Macmillan, 2015)
This is the seventh book in Ann Cleeves' Vera Stanhope series which is now a major ITV detective drama Vera, starring Brenda Blethyn. This case was different from anything Vera had ever worked before. Two bodies, connected but not lying together. As Vera is drawn into the claustrophobic world of this increasingly strange community, she realizes that there may be deadly secrets trapped here.
113566
Keywords: Stanhope, Vera -- Fiction; Police -- Fiction; Women detectives -- England -- Fiction; Murder -- Investigation -- Fiction; Inspectrices de police -- Angleterre -- Romans, nouvelles, etc; England; Detective and mystery stories; Mystery fiction; Fiction